New Zealand Religious Groups’ Responses to the Christchurch Terror Attacks: Inclusion, Exclusion and the State Response to the Mosque Victims - Rivera, Catherine; Oxholm, Theis; Hoverd, Wil (Journal for the Academic Study of Religion, 2023)
This article explores how New Zealand religious leaders and their communities responded to the 15 March 2019 Christchurch mosque shootings. This article analyses qualitative data, drawn from leaders across New Zealand’s diverse religious communities, specifically including minority religions and the non-religious. It utilizes a two-time-period qualitative data collection methodology combining material drawn directly after the attacks with interviews subsequently conducted one year later with a diverse sample of religious leaders (n=14). We offer three findings: 1) Immediate religious community responses to the Christchurch mosque shootings, 2) Religious community reactions and reflections on the state response, and 3) Inclusive and exclusive religious framing of the mosque victims’ Muslim identity. Our findings demonstrate that New Zealand religious communities were universally appalled by the Christchurch mosque attacks, in terms of its human impacts on the Muslim community, but in some cases the recognition and legitimation of the victims’ religious identity were contested.